The Application and Adaptation of Psychological First Aid: The Filipino Psychologists' Experience After Typhoon Haiyan - Hechanova, Ma. Regina (Archīum Ateneo, 2015)
This study examined the experiences, adaptations, observations, and insights on the use of Psychological First Aid (PFA) in the Philippines. Nineteen PFA providers who were trained in the basics of PFA from three major cities in the Philippines took part in this study. Respondents' knowledge about PFA was consistent with the core principles of promoting a sense of safety, calm, self-and community efficacy, connectedness, and instilling a sense of hope. The delivery of PFA was adapted to the Filipino culture through the use of local counseling models, a group-based setup , and the use of mindfulness and relaxation techniques. The respondents highlight the perceived efficacy in using and adapting PFA to support Filipino survivors after a disaster like Typhoon Haiyan.